TEKNIK PENGAWASAN PADA LEMBAGA PENDIDIKAN ISLAM SEBAGAI MEKANISME PENJAMINAN MUTU DI MA ROUDLOTUL MUTA'ALIMIN CLURING BANYUWANGI - Mahmud Abdul Ghofur; M Sidiq Purnomo (Hijri, 2025)
The main objective of this study is to analyse the effectiveness of supervision techniques in Islamic educational institutions as a quality assurance mechanism at MA Roudlotul Muta'alimin Cluring Banyuwangi. This research employs a qualitative approach with a case study design to understand the supervision techniques at MA Roudlotul Muta'alimin Cluring Banyuwangi as a quality assurance mechanism. Primary data were obtained through in-depth interviews with the principal, teachers, the school committee, and students, while secondary data were drawn from school documents and reports. Data were collected through semi-structured interviews, participatory observations, and document studies. Data analysis was conducted thematically through coding, categorisation, and interpretation based on administrative and social aspects. Validity was maintained through triangulation and member checking, resulting in a holistic understanding and practical recommendations for quality assurance in Islamic education.The study at MA Roudlotul Muta'alimin Cluring Banyuwangi shows that supervision techniques play a strategic role in assuring the quality of Islamic education. The implementation of structured supervision improves the quality of learning, with teachers planning material more systematically and adjusting instructional methods to students' needs, thereby enhancing students' understanding and participation. Participatory supervision involving teachers, students, and the school committee strengthens the academic culture, encourages teacher motivation, increases creativity in teaching methods, and fosters student discipline and responsibility. The integration of administrative and social aspects produces a holistic and adaptive supervision mechanism, enabling objective performance evaluation, effective communication with parents, and relevant instructional strategies. The findings affirm that supervision functions as an instrument for teacher professional development, improvement of instructional quality, and the establishment of a sustainable academic culture